The Aldosterone Synthase Inhibitor FAD286 is Suitable for Lowering Aldosterone Levels in ZDF Rats but not in db/db Mice - Hofmann, Anja; Brunssen, Coy; Peitzsch, Mirko; Balyura, Mariya; Mittag, Jennifer; Frenzel, Annika; Jannasch, Anett.; Brown, Nicholas F.; Weldon, Steven M.; Gueneva-Boucheva, Kristina K.; Eisenhofer, Graeme; Bornstein, Stefan R.; Morawietz, Henning (Hormone and Metabolic Research, 2017)
Inhibition of aldosterone synthase is an alternative treatment option to mineralocorticoid receptor antagonism to prevent harmful aldosterone actions. FAD286 is one of the best characterized aldosterone synthase inhibitors to date. FAD286 improves glucose tolerance and increases glucose-stimulated insulin secretion in obese and diabetic ZDF rats. However, there is limited knowledge about the dose-dependent effects of FAD286 on plasma aldosterone, corticosterone, and 11-deoxycorticosterone in ZDF rats and in db/db mice, a second important rodent model of obesity and type 2 diabetes. In addition, effects of FAD286 on plasma steroids in mice and rats are controversial. Therefore, obese Zucker diabetic fatty (ZDF) rats and db/db mice were treated with FAD286 for up to 15 weeks and plasma steroids were evaluated using highly sensitive liquid chromatography-tandem mass spectrometry. In ZDF rats, FAD286 (10 mg/kg/d) treatment resulted in nearly complete disappearance of plasma aldosterone while corticosterone levels remained unaffected and those of 11-deoxycorticosterone were increased ~4-fold compared to vehicle control. A lower dose of FAD286 (3 mg/kg/d) showed no effect on plasma aldosterone or corticosterone, but 11-deoxycorticosterone was again increased ~4-fold compared to control. In contrast to ZDF rats, a high dose of FAD286 (40 mg/kg/d) did not affect plasma aldosterone levels in db/db mice although 11-deoxycorticosterone increased ~2.5-fold. A low dose of FAD286 (10 mg/kg/d) increased plasma aldosterone without affecting corticosterone or 11-deoxycorticosterone. In conclusion, the aldosterone synthase inhibitor, FAD286, lowers plasma aldosterone in obese ZDF rats, but not in obese db/db mice.
Keywords: aldosterone synthase inhibition; steroid hormones; db/db mice; ZDF rats